Pengelolaan Pelayanan Desa dengan Konsep Pdca (Plan, Do, Check And Action) dalam Masa Pandemi Covid-19 di Kelurahan Curug, Kecamatan Bojongsari, Depok - Nidia Sofa; Iis Mariam; Titik Purwinarti; Husnil Barry (Unri Conference Series: Community Engagement, 2021)
In order to support the government's program in tackling the spread of Covid 19, the Curug sub-district, Bojongsari District, Depok mobilized PKK cadres, Posyandu and Karang Taruna in its implementation. However, these cadres have never received education regarding the implementation of service procedures for the community. So that sometimes, miscommunication occurs in the implementation of activities, and there are several complaints from the public regarding the quality of services provided. The D-IV Applied Business Administration (ABT) Study Program offers a solution by providing service management training to sub-district staff, Posyandu cadres, PKK, and Karang Taruna in improving village services to rural communities. Using the Plan, Do, Check and Action (PDAC) concept, it is hoped that the sub-district staff and village cadres can achieve their commitment to excellently serving the community and taking an active role in helping the government overcome Covid 19.